Cataract frequency and subtypes involved in workers assessed for their solar radiation exposure: a systematic review. Issue 8 (16th April 2018) - Modenese, Alberto; Gobba, Fabriziomaria
Abstract: Cataract is currently the primary cause of blindness worldwide, and one of its main risk factors is solar ultraviolet radiation exposure. According to the localization of lens opacities, three main subtypes of cataract are recognized: nuclear, cortical and posterior subcapsular cataract. One of the main determinants of individual long‐term solar radiation exposure is outdoor work. We systematically reviewed scientific literature from the last 20 years to update the recent development of research on the risk of cataract in outdoor workers and on the specific subtypes involved, also investigating the methods applied to evaluate the occupational risk. A total of 15 studies were included in the review, of which 12 showed a positive association. The studies confirm the relationship of long‐term occupational solar radiation exposure with cortical cataract and give new support for nuclear cataract, although no substantial new data were available to support a relation with the posterior subcapsular subtype. In most of the studies, the exposure assessment was not adequate to support a representative evaluation of the ocular risk; however, outdoor work is clearly a relevant risk factor for cataract. Further research providing a better evaluation of the relation between solar radiation exposure levels and lens damage in workers is needed and aimed to establish adequate occupational exposure limits and better preventive measures, studying also their effectiveness.